2016
DOI: 10.1002/jcop.21875
|View full text |Cite
|
Sign up to set email alerts
|

“There goes the fear”: feelings of safety at home and in the neighborhood: The role of personal, social, and service factors

Abstract: Safety has been shown to be an important contributor to mental well‐being and is often identified as a key element of sustainable communities. Drawing on the fear of crime literature this study investigates the determinants of feelings of indoor and outdoor safety for people living in deprived areas, using both cross‐sectional and longitudinal samples from household surveys in 15 communities in Glasgow. Across the different models social cohesion, satisfaction with services, and perceived empowerment emerge as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 53 publications
1
25
1
5
Order By: Relevance
“…Previous literature had shown that outside of their home, women generally feel less safe than men, especially in high‐crime urban neighborhoods (Allik & Kearns, ; Brunton‐Smith & Sturgis, ; Haynie, ; Lane & Meeker, ; Lane et al., ; Schafer et al., ; Warr, ). Yet our study did not show this effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous literature had shown that outside of their home, women generally feel less safe than men, especially in high‐crime urban neighborhoods (Allik & Kearns, ; Brunton‐Smith & Sturgis, ; Haynie, ; Lane & Meeker, ; Lane et al., ; Schafer et al., ; Warr, ). Yet our study did not show this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood perceptions of safety can serve as a proxy for certain neighborhood conditions such as crime, exposure to violence, and concentrated poverty (Drakulich, ; Ross & Mirofsky, ; Rassmussen, Aber, & Bhana, ; Thomas, Caldwell, Jagers, & Flay, ). Neighborhood safety has also been found to be negatively associated with health and well‐being (Burdette, Wadden, Wadden, & Whitaker, ; Duncan, Johnson, Molnar, & Azrael, ; Zhang, Eamon, & Zhan, ), and positively associated with favorable perceptions of the neighborhood walking environment (Brown, Perkins, & Brown, ; Foster & Giles‐Corti, ; Mason et al., ), aesthetic quality (Austin, Furr, & Spine, ; Kuo & Sullivan, 1998; Miles, ), and collective efficacy (Allik & Kearns, ; Pearson, Breetzke, & Ivory, ; Thomas, Caldwell, & Jagers, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety is often listed as a key element of sustainable communities and an important contributor to people's wellbeing, as lacking safety perceptions can have detrimental effects on individuals' wellbeing (Allik & Kearns, 2017). The safety of citizens is thus a "legitimate goal for public policy" (Ben-Arieh, & Shimon, 2014).…”
Section: Positive Safetymentioning
confidence: 99%